Le rôle des politiques publiques dans l’éclatement urbain : l’exemple de la Belgique - Olivier Dubois (Développement Durable et Territoires)
This article tries to synthesize the main factors that explain the extent of urban sprawl in Belgium. This review emphasizes that the present dynamics results from different factors, some of which are ancient. The central place of the public authorities is highlighted, in particular by the way of measures favorable to private ownership. This ancient and central role allows us to draw some guidelines for promoting a new urbanization more in line with the principles of sustainable development.